Bone-Marrow-Derived Mesenchymal Stem Cells Attenuate Behavioral and Cognitive Dysfunction after Subarachnoid Hemorrhage via HMGB1–RAGE Axis Mediation - Harry Jung; Dong Hyuk Youn; Jeong Jin Park; Jin Pyeong Jeon (Life, 2023)
We evaluated the therapeutic effects of bone-marrow-derived mesenchymal stem cells (BMSCs) on behavioral and cognitive function in a mouse model of mild subarachnoid hemorrhage (SAH) and explored the underlying mechanisms in conjunction with the HMGB1–RAGE axis. The SAH models were generated in a total of 126 male C57BL/6J mice via endovascular perforation and evaluated 24 h and 72 h after the intravenous administration of BMSCs (3 × 105 cells). The BMSCs were administered once, at 3 h, or twice, at 3 h and 48 h after the model induction. The therapeutic effects of the BMSCs were compared to those of the saline administration. Compared to saline-treated SAH-model mice, at 3 h, the mice with mild SAH treated with the BMSCs showed significant improvements in their neurological scores and cerebral edema. The administration of the BMSCs decreased the mRNA expression of HMGB1, RAGE, TLR4, and MyD88, as well as the protein expression of HMGB1 and phosphorylated NF-kB p65. Furthermore, the numbers of slips per walking time, impairments in short-term memory, and the recognition of novel objects were improved. There was some improvement in inflammatory-marker levels and cognitive function according to the BMSCs’ administration times, but no large differences were seen. The administration of BMSCs improved behavioral and cognitive dysfunction by ameliorating HMGB1–RAGE axis-mediated neuroinflammation after SAH.